2013
DOI: 10.1002/hep.26487
|View full text |Cite
|
Sign up to set email alerts
|

Radiological-pathological analysis of WHO, RECIST, EASL, mRECIST and DWI: Imaging analysis from a prospective randomized trial of Y90 ± sorafenib

Abstract: Aim To compare radiological and pathological changes and test the adjunct efficacy of Sorafenib to Y90 as a bridge to transplantation in HCC. Methods 15 patients with 16 HCC lesions randomized to Y90 without (Group A, n=9) or with Sorafenib (Group B, n=7). Size (WHO, RECIST), enhancement (EASL, mRECIST) and diffusion-weighted imaging criteria (ADC) measurements were obtained at baseline, 1 and every 3 months after treatment until transplantation. Percentage necrosis in explanted tumors was correlated with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 28 publications
6
47
1
1
Order By: Relevance
“…Some studies have confirmed the usefulness of these criteria for yttrium radiation [20,21], but radiological studies have failed to demonstrate a similar value in external beam radiation. Studies have concluded that mRECIST is useful for correlation with prognosis and as a framework for clinical trial design, but should not be used for routine clinical practice due to its inaccuracy in estimating viable tumor correctly [22,23]. This may be due to the problem of halo formation postradiation where a normal rim of enhancement develops around the region irradiated.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have confirmed the usefulness of these criteria for yttrium radiation [20,21], but radiological studies have failed to demonstrate a similar value in external beam radiation. Studies have concluded that mRECIST is useful for correlation with prognosis and as a framework for clinical trial design, but should not be used for routine clinical practice due to its inaccuracy in estimating viable tumor correctly [22,23]. This may be due to the problem of halo formation postradiation where a normal rim of enhancement develops around the region irradiated.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum response in terms of size reduction could take 4-6 months to be achieved [7]. Alternative criteria have been proposed, such as EASL, modified RECIST, and the Choi criteria [1,41,42]. Conflicting results have been published concerning the comparison of these new criteria, but overall, authors agree that focusing on the viable part of the lesion allows more accurate evaluation than RECIST does.…”
Section: Areas Of Controversy and Future Developmentmentioning
confidence: 96%
“…Conflicting results have been published concerning the comparison of these new criteria, but overall, authors agree that focusing on the viable part of the lesion allows more accurate evaluation than RECIST does. Riaz et al showed better correlation of these new criteria with pathological necrosis, compared with RECIST or World Health Organization criteria [12]; however, a second study failed to reproduce these results[42]. Other functional modalities, such as diffusion-MRI or perfusion-CT have also been proposed, as well as use of the alpha-fetoprotein response, but their usefulness still needs to be clarified.…”
Section: Areas Of Controversy and Future Developmentmentioning
confidence: 99%
“…Lewin et al [107] reported a significant f (perfusion fraction) increase in responders at 2 wk and at 2 mo of sorafenib therapy, whereas a decrease was noted in non-responders at the same time intervals. Vouche et al [108] reported that ADC values did not change 1 and 3 mo after 90 Y TARE or 90 Y TARE plus sorafenib treatments. These results may be explained by the pleiotropic anti-angiogenic actions of sorafenib, which destroys tumor vessels and improves the integrity of basement membranes of the remaining microvessels, thus leading to less "water leakage" from the perfusion pool.…”
Section: Primary Liver Tumorsmentioning
confidence: 99%
“…Sunitinib seems to induce K trans and Kep decrease and ADC increase [113,114] ; these modifications can be assessed even at a very early stage (after 2 wk of treatment). Lewin et al [107] 12 IVIM f increase HCC sorafenib Vouche et al [108] 15 DWI ADC increase HCC 90 Y TARE ± sorafenib…”
Section: Primary Liver Tumorsmentioning
confidence: 99%